2017
DOI: 10.5455/msm.2017.29.119-123
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and Monthly Variation in Stroke and its Subtypes-10 Year Hospital-Based Study

Abstract: Background and Objectives:There is no evidence of long-term studies of seasonal variations in stroke in Iran. Hence, the aim of this study was to determine the seasonal and monthly variation of 28-day mortality in Isfahan, Iran.Methods:From 2003 to 2013, In a Hospital-based retrospective study which was conducted by Isfahan Cardiovascular Research Center(ICRC), 24186 cases with first-ever stroke were recruited. Multinomial logistic regression was used to calculate odds ratios (OR) with 95% confidence intervals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…These findings are consistent with a study by Raj et al [15] Few studies have demonstrated no significant seasonal variations in stroke cases or identified summer as the season with most cases of stroke. [1,4,17] Similar results to ours, showing high rates of stroke in winter and spring, were obtained in Poland and Hungary. [18] The above finding also corresponds with our results and those of Moinuddin et al [19] Stroke, like any other non-communicable disease, has a complex, multifactorial aetiology.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…These findings are consistent with a study by Raj et al [15] Few studies have demonstrated no significant seasonal variations in stroke cases or identified summer as the season with most cases of stroke. [1,4,17] Similar results to ours, showing high rates of stroke in winter and spring, were obtained in Poland and Hungary. [18] The above finding also corresponds with our results and those of Moinuddin et al [19] Stroke, like any other non-communicable disease, has a complex, multifactorial aetiology.…”
Section: Discussionsupporting
confidence: 87%
“…These findings were similar to those of a recent study in Iran. [1] While we found the prevalence of diabetes to be high in white female stroke patients, hypertension was found to be the most common risk factor in black females. Table 5 indicates considerable monthly variation in risk factors, with high proportions of cases in patients with hypertension, diabetes and heart problems in the winter months, in accordance with the findings of Bahonar et al [1] and Wang et al [11] In contrast, there were few stroke patients with these risk factors in the month of November.…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…Even though seasonal variations affect the entire human physiological systems, the cardio-vascular systems, cardio-respiratory systems, and circadian rhythms are most sensitive to these seasonal changes. In recent days, there is an impressive pattern of seasonal rhythm in hospitalizations of patients with cardio-vascular and cardio-respiratory diseases or disorders, with a notable increase in winter [811].…”
Section: Introductionmentioning
confidence: 99%